PENGARUH KONDISI KEUANGAN PERUSAHAAN, UKURAN PERUSAHAAN, PERTUMBUHAN PERUSAHAAN DAN REPUTASI KAP TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015-2017 - Akbar, Rivaldi; Ridwan, Ridwan (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2019)
This study aims to examine the effect of financial distress, size firms, growth companies, and reputation public accounting firm on acceptance of going concern opinion. The method of this research is a quantitativ approach and SPSS as an analysis tool. Object under study is a mining companies listed on Indonesia Stock Exchange during the periode 2015-2017,as many 33 companies for 3 years with 99 total sample. Testing is done by using logistic regresion analysis by using SPSS version 25.The result showed that the financial distress proxied by the calculation of altman modification model has no significant on the acceptance of going concern audit opinion. Second, the firm size has significant and positive effect on the acceptance of going concern opinion. Third, the growth companies has significant and negative effect on the acceptance of going concern opinion. Finally, the reputation of the public accounting firm proxied at the scale of the public accounting firm has no significant effect on the acceptance of going concern audit opinion